THE SELECTION OF CHARACTERISTIC FRAGMENTS IN THE IMAGE OF A HUMAN FACE - Швець, Валеріян Анатолійович; Німченко, Тетяна Васильовна; Васянович, Віталій Васильович (Ukrainian Information Security Research Journal, 2015)
The development of information technology is closelytouches on the issues of information security part, which isthe control system and access control objectives for informationand activities. Control systems and access controlfor use biometric identification by the image of a humanface. However, as practice shows, the control system andaccess control has one major drawback is the possibility ofan attacker tampering with the image of a real person hisportrait, that is, the attempt to present a portrait of a realperson, which can lead to the penetration of the attackeron the object information activities. The article discussesthe implementation of the detector of the human face inthe image to the possibilities of its implementation directlyby the controller of the camera and the selection of characteristicfragments in the software system to improve thereliability of the identification.